Functionalized TiO2 nanoparticles by single-step hydrothermal synthesis: the role of the silane coupling agents - Dalod, Antoine R. M.; Henriksen, Lars; Grande, Tor; Einarsrud, Mari-Ann (Beilstein Journal of Nanotechnology, 2017)
A simple, robust and versatile hydrothermal synthesis route to in situ functionalized TiO2 nanoparticles was developed using titanium(IV) isopropoxide as Ti-precursor and selected silane coupling agents (3-aminopropyltriethoxysilane (APTES), 3-(2-aminoethylamino)propyldimethoxymethylsilane (AEAPS), and n-decyltriethoxysilane (DTES)). Spherical nanoparticles (ca. 9 nm) with narrow size distribution were obtained by using DTES or by synthesis performed without silane coupling agents. Rod-like nanoparticles along with 9 nm spherical nanoparticles were formed using aminosilane coupling agents because of a combination of oriented attachment of nanoparticles and specific adsorption of the aminosilane on crystallographic faces of anatase nanoparticles. The nanoparticles were functionalized in situ and became hydrophobic as silanes reacted to form covalent bonds on the surface of TiO2. The versatility of the aqueous synthesis route was demonstrated, and by selecting the type of silane coupling agent the surface properties of the TiO2 nanoparticles could be tailored. This synthesis route has been further developed into a two-step synthesis to TiO2–SiO2 core–shell nanoparticles. Combustion of the silane coupling agents up to 700 °C leads to the formation of a nanometric amorphous SiO2 layer, preventing growth and phase transition of the in situ functionalized nanoparticles.
Keywords: core–shell nanoparticles; functionalized nanoparticles; hydrothermal synthesis; oriented attachment; silane coupling agent